Network of observations on the atmospheric electrical parameters during geomagnetic storm on 5 April 2010. Issue 3 (30th March 2016) - Victor, N. Jeni; Manu, S.; Frank‐Kamenetsky, A. V.; Panneerselvam, C.; Anil Kumar, C. P.; Elango, P.
Abstract: The effects of a geomagnetic storm on the variation of the atmospheric electric field over Maitri (70°45′S, 11°44′E), Dome C (75°06′S, 123°20′E), and Vostok (78°27′S, 106°52′E) Antarctic research stations are presented in this paper. For the first time, the paper reports the simultaneous observations of the atmospheric electric field/potential gradient (PG) over the three high‐latitude stations at the Southern Hemisphere, and its associated changes due to a substorm phenomenon. PG data obtained from these three stations under fair‐weather conditions on 5 April 2010 are analyzed. The duration of geomagnetic disturbance is classified into three intervals, which contains three consecutive substorms based on the magnetic records of the Maitri station. The substorm is directly related to an enhancement of the magnetospheric convective electric field at high latitude, generally controlled by the solar wind parameters. It is found that the variation in the amplitude of PG depends on the magnetic latitude during substorm onset. During the substorm expansion phase, when the convection cell is at overhead, PG is significantly enhanced due to the downward mapping of the ionospheric horizontal electric field. The present observation demonstrated the changes on PG due to the spatial extension of the convection cell from high latitudes up to middle latitudes. Key Points: Simultaneous observations of the atmospheric electric field Downward mapping of ionospheric horizontal electric field Magnetic latitude dependence during substorm onset